Population pharmacokinetics of vancomycin in patients with external ventricular drain‐associated ventriculitis. Issue 6 (13th December 2020) - Jalusic, Kris Oliver; Hempel, Georg; Arnemann, Philip‐Helge; Spiekermann, Christina; Kampmeier, Tim‐Gerald; Ertmer, Christian; Gastine, Silke; Hessler, Michael
Abstract : Background: To determine the distribution of vancomycin into the cerebrospinal fluid (CSF) in patients with external ventricular drain (EVD)‐associated ventriculitis, the pharmacokinetics of vancomycin were evaluated and covariate relationships explored. Methods: For the population pharmacokinetic model patients were recruited in a neurocritical care unit at the University Hospital of Muenster in the period between January 2014 and June 2015. All patients had a clinical evidence of EVD‐associated ventriculitis. Population pharmacokinetic analysis of vancomycin was performed using NONMEM. Results: A total of 184 blood and 133 CSF samples were collected from 29 patients. The final population pharmacokinetic model is a three‐compartment model with linear elimination. Creatinine clearance (ClCr ) and CSF‐lactate were detected as significant covariates, showing that the total vancomycin plasma clearance (Cl) depends on ClCr and furthermore the clearance (Cldif ) between the central and CSF compartment correlates with CSF lactate concentration. Based on the final model, the following values were estimated by NONMEM: Cl = 5.15 L/h, Q (intercompartmental clearance) = 3.31 L/h, Cldif = 0.0031 L/h, V central = 42.1 L, V CSF = 0.32 L and the value of V peripheral was fixed to 86.2 L. With the developed pharmacokinetic model, area under the curve (AUC) values as well as CSF trough levels were simulated. Conclusion: Based on our analysis, the dosing of vancomycin should be referred to the degree of inflammation (derived from the CSF lactate concentration) and renal function (derived from ClCr ).